2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125075
|View full text |Cite
|
Sign up to set email alerts
|

A motorized and easy-docking wheelchair drive for persons with lower-limb disabilities

Abstract: The aim of this study is to develop a driving module that can be attached to a manual wheelchair with an easydocking mechanism to assist persons with lower-limb disabilities. The driving module consists of a motorized driving mechanism, embedded control boards, and an easy-docking mechanism, which can together be used to convert a manual wheelchair to an electrical wheelchair. The core of the easy-docking mechanism comprises the snatch locks and yokes, with which the driving module can be attached in front of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…According to a market survey, the cost is reduced to the achievable US $400 compared to a minimum US $1100 in the United States. Kim et al [8] developed a driving module attached to a manual wheelchair with an easy locking mechanism to assist persons with lower limb disabilities. The driving module was tested to evaluate its performance, and the results showed that the developed system helped increase the mobility of persons with lower limb disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…According to a market survey, the cost is reduced to the achievable US $400 compared to a minimum US $1100 in the United States. Kim et al [8] developed a driving module attached to a manual wheelchair with an easy locking mechanism to assist persons with lower limb disabilities. The driving module was tested to evaluate its performance, and the results showed that the developed system helped increase the mobility of persons with lower limb disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The wheelchair was designed to be driven by a dc brushless. To be stable, the wheelchair required a controller consisting of a microprocessor (MPU), an accelerometer sensor, and a DC brushless motor driver (Kim et al 2015).…”
Section: Introductionmentioning
confidence: 99%